Effect of Welding Speed on Microstructure and Mechanical Properties due to The Deposition of Reinforcements on Friction Stir Welded Dissimilar Aluminium Alloys - Baridula, Ravinder Reddy; C. K. M., Faizal; Ramaraju, Ramgopal Varma; Abdullah, Ibrahim (EDP Sciences, 2017)
The strength of the welded joint obtained by solid state stir welding process was found to be improved as compared to fusion welding process. The deposition of reinforcements during friction stir welding process can further enhance the strength of the welded joint by locking the movement of grain boundaries. In the present study, the aluminium alloys AA2024 and AA7075 were welded effectively by depositing the multi-walled carbon nanotubes in to the stir zone. The mechanical properties and microstructures were studied by varying the traverse speed at constant rotational speed. The results show that rotating tool pin stirring action and heat input play an important role in controlling the grain size. The carbon nanotubes were found to be distributed uniformly at a welding speed (traverse speed) of 80mm/min. This enhanced the mechanical properties of the welded joint. The microstructure and Electron dispersive X-ray analysis(EDX) studies indicate that the deposition of carbon nanotubes in the stir zone was influenced by the traverse speed.